Authority and democracy in popular culture: An approach from the Andean culture - Ansión, Juan (1989)
This text is a first balance of a reflection of many years that starts from the land of Ayacucho and seeks to connect with the country looking at it in the light of the great popular experiences of recent decades. The challenge is to think about the country from the popular perspective and to think about the popular perspective from its Andean roots. They are inconclusive reflections, since they are a new starting point for research on popular political culture in Lima. Therefore, they should be read as guiding hypotheses, as suggestions for research.